Contested Nationalism: The “Irish Question” in St. John’s, Newfoundland, and Halifax, Nova Scotia, 1919-1923 - Mannion, Patrick (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2015)
From 1919 until 1923, Irish nationalist networks flourished in St. John’s and Halifax. This article is a comparative study of responses to the Irish Question in the two cities, and it suggests that Irish identities did not evolve in isolation. Rather, their intensity and expression were profoundly influenced by the interaction of local, regional, national, and transnational ethnic networks. Although those of Irish descent who participated in the Self-Determination for Ireland League meetings, rallies, and lectures tended to be at least a generation removed from their ancestral homeland, they remained part of a transnational Irish diaspora until well into the 20th century.